Utilization Of Vermicomposting Derived Liquids As Nutrient Solution In Soil-Less Culture - Quaik, Shlrene (2014)
Pre-composted cow dung was used as the substrates in preparing vermicornposting derived liquids. Composition of vennicomposting derived liquids are often depends on the substrate used during the preparation. Vermicomposting derived liquids (vermiwash (VW) and vermicomposting leachate (VL» contain high amount of plant nutrients. Not only these liquids are suitable to be used as nutrient supplements for plants for growth promoting. they also have the potential to be used as nutrient solution in soil-less culture. The main objective in this study is to determine the effects of VW and VL towards plant growth in soil-less culture. Analyses had confirmed the presence of high amount of nutrients (P. Ca. Mg. Na, Fe and K) in cow dung (13.4 ± 0.08 mg g.1 Total P. 42.92 ± 0.02 mg g.1 Ca. 4.24 ± 0.03 mg g.1 Mg. 18.9 ± 0.12 mg g.1 Na, 6.034 ± 0.08 mg g.1 Fe and 99.96 ± 1.76 mg g-I K). The presence of trace elements (0.10 ± 0.02 mg g-I Ph) was also detected. Chemical analyses confirmed the presence of 0.032 ± 0.0 I % N. 4.36 ± 0.00 mg L:I total P, 215.33 ± 5.37 mg L-I K. 107.93 ± 2.27 mg L-I Na. 172.87 + 6.43 mg 1;1 Cu, 0.188 :1: 0.03 mg L·I Mg, 0.025 ± 0.00 mg L-I Cu and 0.114 :1: 0.01 mg 1:1 Zn in VW and 0.013 ± 0.01 % N. 3.53 ± 0.00 mg L-I total P, 0.20 ± 7.01 mg L-I K. 111.73 ± 3.02 mg L-I Na. 167.63 ± 1.95 mg L-I Ca. 0.217 ± 0.00 mg 1;1 Mg. 0.030 ± 0.00 mg L-I Cu and 0.248 ± 0.0 I mg L-I Zn in VL. Utilization of VW and VL with dilution (10, 20 and 30%) showed effect towards shoot length. root weight, shoot weight and total biomass of onion bulb (Allium cepa).